OPINION LEADERSHIP MEMODERASI eWOM INTENTION (STUDI PADA BOMBARU BAR DAN RESTO BENGKULU, INDONESIA) - Ryan Vernando Putra; Muhartini Salim; Sularsih Anggarawati (Universitas Mercu Buana, 2020)
Abstract. The purpose of this study was to examine the influence of Self-Relevant Value, Quality Value and Perceived Informational Utility on Electronic Word-Of-Mouth Intention moderated by Opinion Leadership in Bombaru Bars and Restaurant Bengkulu, Indonesia consumers. The respondents of this study were 17-45 years old. Respondent data were collected by the survey questionnaire provided. After adopting the listwise deletion method through Mahalanobis Distance on SEM-AMOS, 133 questionnaires that could be used were available for analysis. Data analysis used Confirmatory Factor Analysis (CFA), assessment of normality, and regression weights. The Result indicate that (1) Self-relevant Value has a positif effect on eWOM Intention; (2) Quality Value has a positif effect on eWOM Intention; (3) Perceived Informational Utility has a postif effect on eWOM Intention; (4) Opinion Leadership moderates the influence of Self-relevant Value on eWOM Intention; (5) Opinion Leadership moderates the influence of Quality Value on eWOM Intention; (6) Opinion Leadership moderates the influence of Perceived Informational Utility on eWOM Intention.Keyword: eWOM Intention, Opinion Leadership, Perceived Informational Utility, Quality Value, and Self-relevant Value.